Effect of Biochar, Potting Mixture and their Blends to Improve Ocimum basilicum Growth in Sandy Soil - Mohammad Danish (2879303) (2024)
Biochar has received significant interest as a soil amendment but its relative performance to addition of high-quality soil is not well assessed. This study compared different loadings of cabbage-waste biochar produced at 360 °C against potting mixture (PM) as amendments to enhance basil (Ocimum basilicum) growth in sandy soil. Pot tests for six conditions of biochar, PM or their blend were tested at both 2% or 6% loading, plus a control, with soil and plant characteristics monitored. The combination of 6% biochar and 6% PM increased seed germination by 85% compared to the control, while 6% biochar applied in sandy soil reduced seed germination by 29%. However, significant benefits were realized later in the growing stage in comparison to the control and most other tested conditions. The 6% application of biochar to the soil enhanced leaf chlorophyll and carotenoid contents, membrane stability index, and leaf relative water content by 198%, 150%, 15%, and 5% over the control, respectively. The highest shoot and total biomass were achieved with the combined application of 6% biochar and PM, followed by 6% biochar only. When comparing only application of biochar or PM, biochar was the more favorable soil amendment at both 2% and 6% loadings. Biochar was also effective at enhancing plant uptake of beneficial nutrients, while immobilizing Al, which is detrimental, in the soil. Overall, biochar is a better soil amendment for sandy soil than equivalent quantities of PM, but mild benefits occur through their combined application. Other Information Published in: Journal of Soil Science and Plant Nutrition License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42729-024-01670-8 Additional institutions affiliated with: Materials Core Labs - HBKU